Faktor-Faktor Yang Berhubungan Dengan Penggunaan Gadget Terhadap Interaksi Sosial Pada Anak Usia Sekolah - Lestari, Indri Puji; Novitri, Novitri; Fitra Amelia (Institut Citra Internasional, 2024)
Gadgets have now become a daily necessity for modern society, so most parents have introduced gadgets to their children from an early age. Gadgets are not only used by adults, but children also have the same interests. As a result, the use of gadgets with long intensity with the type of application use without parental supervision will affect social interaction in children. The purpose of this study was to determine the relationship between intensity, type of use and gender in the use of gadgets on social interaction in school-age children. This study was conducted using a cross-sectional design and chi-square test with the results of univariate and bivariate analysis. The research sample amounted to 47 people. The instrument in this study used a questionnaire sheet consisting of a questionnaire sheet of intensity, gender, type of use and social interaction. The results of the study concluded that there was a relationship between the intensity of p-value=(0.001), the type of use p-value=(0.022) and gender p-value=(0.002) in the use of gadgets on social interaction in school-age childrenju. Conclusion there is a relationship between intensity, type of use and gender in the use of gadgets on social interaction in school-age children. The suggestion from the research is that parents can pay more attention to and monitor school-age children by supervising when children use smartphones.